Protective effects of mouthwash formulations of Syzygium polyantha (L.) and Piper betel (L.) on oral microbiota-induced gingivitis - Megananda Hiranya Putri; Neneng Nurjanah; Dewi Sodja Laela; Susi Sukmasari (PAGEPress Publications, 2023)
Using a combination of natural ingredients as a mouthwash was expected to have a synergistic effect in preventing gingivitis, a common oral disease. The objective of this study was to elucidate the anti-inflammatory effect of different proportions of mouthwash infusions: F1 (75% Syzygium polyantha and 25% Piper betle) and F2 (25% Syzygium polyantha and 75% Piper betle) on oral microbiota causing gingivitis. Twenty-four Rattus norvegicus were divided into four groups, and bacteria were injected into the periodontal sulcus. The anti-inflammatory effect was assessed by calculating the reduced number of polymorphonuclear (PMN) leukocytes. A cytotoxicity test was carried out on the normal fibroblast cell line 3T3-L1. There were no significant differences in the decreased number of PMN leukocytes (p = 0.079 > 0.05). Both F1 and F2 showed results of cell viability approaching 100% of living cells at concentrations of 0.29 ppm and 0.04 ppm, equivalent to 0.058% and 0.029%, respectively. This study concluded that both formulations of Syzygium polyantha and Piper betle have potential effects on gingivitis prevention. They had an effectiveness level almost similar to Chlorhexidine gluconate 2%. The toxicity value of formulation F1 is superior to that of formulation F2. Further studies concerning the toxicity of the mixtures and their effect on oral biofilm are needed.